Railroad postcards in the age of steam - Grant, H. Roger, 1943- (University of Iowa Press, 1994)
"This lavish volume is the first general book-length work devoted to the once-ubiquitous railroad picture postcard. It is comprised of an introductory essay and an album of cards. The former fully examines the nature of the postcard craze, which reached its zenith about 1910, and discusses why images of American railroads played such an important part in the card phenomenon. The album divides an engaging assortment of more than 150 representative views into five sections: "Trains and Rolling Stock," "Depots and Railway Structures," "The Railroad Corridor," "People and Railroads," and "The Lighter Side of Railroading."" "Railroad historians, train enthusiasts, postcard collectors, and all other readers will find much to interest them in this selection of images. Not only are the cards themselves visually striking, but they convey a sense of how important railroads once were to the nation's citizenry. The sight of steaming locomotives and the hustle and bustle associated with "train time" caused hearts to quicken. These feelings made views of railroad scenes popular with buyers of postcards and now with latter-day railroad fans and card collectors."--Jacket